2013
DOI: 10.3390/f4030710
|View full text |Cite
|
Sign up to set email alerts
|

Indicators and Determinants of Small-Scale Bamboo Commercialization in Ethiopia

Abstract: Abstract:Bamboo is an abundant resource in Ethiopia and has a great potential for commercialization, which can drive rural development. In view of these realities, this study analyzed the state and determinants of small-scale bamboo commercialization in Ethiopia. Data were collected from three major bamboo-growing districts (Awi, Sidama, and Sheka) and four urban centers (Masha, Hawassa, Bahir Dar, and Addis Ababa) via semi-structured interviews, group discussions, and questionnaire surveys with key actors alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 25 publications
(29 reference statements)
2
11
0
4
Order By: Relevance
“…However, this cannot benefit majority of the communities since most of them cannot process different products. This is in agreement with the study of Endalamaw et al (2013) and Tinsley (2015). This showed that Ethiopian bamboo utilization is still limited primarily due to low value addition and weak local market networks.…”
Section: Market Demand Of Highland Bamboosupporting
confidence: 93%
See 1 more Smart Citation
“…However, this cannot benefit majority of the communities since most of them cannot process different products. This is in agreement with the study of Endalamaw et al (2013) and Tinsley (2015). This showed that Ethiopian bamboo utilization is still limited primarily due to low value addition and weak local market networks.…”
Section: Market Demand Of Highland Bamboosupporting
confidence: 93%
“…In addition to key informants, the household survey revealed that most farmers in the domesticated system obtained their bamboo products from privately owned sources. This result is in line with the study conducted by Endalamaw et al (2013). They stated there was poor management of bamboo in Ethiopia; people could not apply any conservation and protection strategy besides traditional management system.…”
Section: Less Awareness Level Of the Peoplesupporting
confidence: 87%
“…Due to its high altitude location and climate, the major crops that grow in this area are predominately teff, barley, peas, and potatoes. Injibara is well-connected to nearby towns and markets, with easy access to transportation and well-paved roads for the movements of products from production to consumption [20]. Figure 3 shows a map of the Amhara region.…”
Section: Research Areamentioning
confidence: 99%
“…A partir de ces localités, des personnes impliquées dans la chaîne de valeurs bambou de chine ont été interrogées. La méthode d'enquête utilisée est celle des questionnaires semi-structurés (Gbesso et al, 2017), des interviews et des observations (Adomou et al, 2012;Tefera et al, 2013).…”
Section: Collecte De Donnéesunclassified